THE CONCEPT OF LEGAL PLURALISM IN INDONESIA IN THE NEW SOCIAL MOVEMENT - Flambonita, Suci (Jurnal Analisa Sosiologi, 2021)
As a multicultural country, legal pluralism in Indonesia should be placed in the perspective of a new social movement, which lies as the abstraction of collective subjects to strive for emancipation. Experience has shown that many policies and political laws concerning natural resources do not provide enough room for the representation of indigenous peoples. As the new social movement in the context of multiculturalism, fighting for socioeconomic and natural resource redistribution is as important as providing spaces to foster cultural struggle in terms of fighting discrimination against indigenous peoples. In Dutch legal pluralism theory is termed as theorie van het rechtspluralisme. Lawrence M. Friedman has proposed a definition of legal pluralism as the presence of different legal systems and cultures in a single political community. This research uses the social legal method with a conceptual and historical approach. According to John Griffiths, legal pluralism is the presence of more than one legal rule in a social circle. Further, the concept of legal pluralism does not promote a dichotomy between state law on the one side and folk law and religious law on the other side.Â Keywords: concept, legal, pluralismÂ AbstrakIndonesia sebagai negara yang multikulturalisme hendaknya pluralisme hukum diletakkan dalam perspektif the new social movement yang bertumpu sebagai abstaksi subyek yang secara kolektif demi memperjuangkan emansipasi. Berdasarkan pengalaman, banyak kebijakan dan politik hukum atas sumber daya alam tidak memberi ruang representasi terhadap masyarakat hukum adat. Sebagai the new social movement dalam konteks multikulturisme tidak hanya penting dalam memperjuangkan redistribusi sosial ekonomi dan sumber daya alam, tetapi juga memberi ruang munculnya gerakkan untuk memperjuangkan cultural struggle (tantangan budaya) diskriminasi terhadap masyarakat hukum adat. Lawrence M. Friedman menyajikan pengertian pluralisme hukum yang berarti â€œadanya sistem-sistem atau kultur hukum yang berbeda dalam sebuah komunitas politik tunggalâ€. Metode penelitian menggunakan sosial legal dengan pendekatan konseptual dan sejarah. Pluralisme hukum oleh John Griffiths, diartikan bahwa hadirnya lebih dari satu aturan hukum dalam sebuah lingkaran sosial, Selanjutnya konsep pluralisme hukum tidak lagi mengedepankan dikotomi antara sistem hukum negara (state law) di satu sisi dengan sistem hukum rakyat (folk law) dan hukum agama (religious law) di sisi yang lain.Â Kata Kunci: Konseptual, Pluralisme, Hukum